Odorant-binding Protein 10 From Bradysia odoriphaga (Diptera: Sciaridae) Binds Volatile Host Plant Compounds. Issue 1 (2nd February 2023) - Zhu, Jiaqi; Wang, Fu; Zhang, Youjun; Yang, Yuting; Hua, Dengke
Abstract: Bradysia odoriphaga (Diptera: Sciaridae) is a major insect pest of seven plant families including 30 commercial crops in Asia. The long-term use of chemical pesticides leads to problems such as insect resistance, environmental issues, and food contamination. Against this background, a novel pest control method should be developed. In insects, odorant-binding proteins (OBPs) transport odor molecules, including pheromones and plant volatiles, to olfactory receptors. Here, we expressed and characterized the recombinant B. odoriphaga OBP BodoOBP10, observing that it could bind the sulfur-containing compounds diallyl disulfide and methyl allyl disulfide with Ki values of 8.01 μM and 7.00 μM, respectively. Homology modeling showed that the BodoOBP10 3D structure was similar to that of a typical OBP. Both diallyl disulfide and methyl allyl disulfide bound to the same site on BodoOBP10, mediated by interactions with six hydrophobic residues Met70, Ile75, Thr89, Met90, Leu93, and Leu94, and one aromatic residue, Phe143. Furthermore, silencing BodoOBP10 expression via RNAi significantly reduced the electroantennogram (EAG) response to diallyl disulfide and methyl allyl disulfide. These findings suggest that BodoOBP10 should be involved in the recognition and localization of host plants.